KONSEP PENDIDIKAN KARAKTER DALAM TEORI TRIPUSAT PENDIDIKAN KI HAJAR DEWANTARA DAN IMPLIKASINYA TERHADAP PENDIDIKAN MORAL DI ERA 5.0 - Khafid, Anhar; Rohman, Akhmad Dalil; Maulana, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Both formal and non-formal education must implement character education. In life, good character and morals are the most important things. The application and implementation of moral education includes three environments, namely the family, school, community environments. With moral education, it is expected to be able to create children who are moral and have good morals so that they are useful for others. The purpose of this study is to describe the concept of character education in Ki Hajar Dewantara's tri-center theory of education and its implications for moral education in the 5.0 era. The research method used is descriptive qualitative research with a literature survey technique. Data collection techniques are sourced from journals, books, and other scientific articles. Based on a review of several scientific works, it was found that character education must be arranged and formulated clearly, such as the tri-center education paradigm pioneered Ki Hajar Dewantara. Based on research conducted by researchers through a review of various literature, it can be concluded that the flow of globalization can change children's character and morals. With this, every child certainly needs to be given good character education for the sake of their own and the nation's sustainability in the future. Through the concept of character education initiated by Ki Hadjar Dewantara, namely the three centers of education, it can provide a good impact. The three centers of education are the most important thing in children's character education because there are three elements in it, namely family, school and also society.